2018
DOI: 10.1161/circresaha.118.311339
|View full text |Cite
|
Sign up to set email alerts
|

Tbx20 Is Required in Mid-Gestation Cardiomyocytes and Plays a Central Role in Atrial Development

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 67 publications
(96 reference statements)
3
37
0
Order By: Relevance
“…This provides an excellent in vitro model for studying various molecular mechanisms of heart. Cardiomyocyte culture has become a basic method for investigating cardiac physiology and pathology, and it provides an ideal model for the study of heart development, differentiation, and metabolism (Boogerd et al 2018 ). Therefore, the cultivation of cardiomyocytes has gradually become a useful model for studying myocardial injury (Liu et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This provides an excellent in vitro model for studying various molecular mechanisms of heart. Cardiomyocyte culture has become a basic method for investigating cardiac physiology and pathology, and it provides an ideal model for the study of heart development, differentiation, and metabolism (Boogerd et al 2018 ). Therefore, the cultivation of cardiomyocytes has gradually become a useful model for studying myocardial injury (Liu et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we find that tbx20 induction is not only localized to the injured myocardium, but also detectable in the atrial epicardium following ventricle injury. During development, tbx20 is expressed in epicardial cells surrounding the atrioventricular canal groove (Yamagishi et al, 2004;Boogerd et al, 2018), but the function of epicardial tbx20 is still unclear. Previous studies indicate that epicardium is required for heart regeneration in zebrafish (Kikuchi et al, 2011a;Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that TBX20, a member of the Tbox transcription factor family plays also a key role in atrial development [50]. Tbx20 function in ventricular cardiac myocytes has been investigated earlier.…”
Section: Transcription Factors Involved In Atrial Development and Dismentioning
confidence: 99%
“…While overexpression of Tbx20 in adult cardiac myocytes induced proliferation and improved cardiac function after myocardial infarction [52]. Besides the directly activating function of myocyte proliferation genes, Boogerd et al showed that Tbx20 directly represses a cardiac progenitor gene program in cardiac myocytes and activates atrial and ventricular specific genes for the establishment or maintenance of atrial and ventricular identity [50]. Interestingly, at E10.5 and E11.5, atria from Tbx20 cKO mice showed reduced levels of COUP-TFII.…”
Section: Transcription Factors Involved In Atrial Development and Dismentioning
confidence: 99%
See 1 more Smart Citation